# Integrating factor change of terminals

#### HallsofIvy

MHF Helper
You know you can't use "T" as variable because it is used as one of the bounds on the integral. If it is specifically, "u" that you are worrying about, any letter other that "t" or "T" could be used.

• 1 person

#### mkmath

How did I know that I can't use "T" as the variable given that in the first equation I am taking a derivative with respect to "T" on the right hand side?

But I think I can see it if I work backwards:

$$\displaystyle \log{P(t,T)} = -\int_{t}^{T}f(t,u)du$$

$$\displaystyle \log{P(t,T)} = -g(t,t) + g(t,T) + C$$

where $$\displaystyle f(t,u) = \frac{\partial g(t,u)}{\partial u}$$.

I know that at $$\displaystyle T=t, \log{P(t,t)} = 0$$ so $$\displaystyle C=0$$

Next take the partial derivative of both sides with respect to "T" such that

$$\displaystyle \frac{\partial \log{P(t,T)}}{\partial T} = -\frac{\partial g(t,t)}{\partial T} + \frac{\partial g(t,T)}{\partial T}$$

$$\displaystyle \frac{\partial \log{P(t,T)}}{\partial T} = f(t,T)$$

by our earlier definition of $$\displaystyle f(t,u) = \frac{\partial g(t,u)}{\partial u}$$.

Comments welcome. Thanks again 